Selectivity of herbicides to native tree species in Brazil - Oliveira, L.; Silva, A. C. [UNESP]; Gonçalves, C. G.; Pereira, M. R.R.; Martins, D. [UNESP] (FapUNIFESP (SciELO), 2019)
Weeds are one of the main obstacles in the recovery of degraded areas. This research aimed to study the selectivity of herbicides on Trema micrantha (Jamaican nettletree), Schinus molle (Peruvian peppertree), and Apuleia leiocarpa (garapeira) seedlings. An experiment was installed in Junqueirópolis and another in Jaboticabal/SP, Brazil. The experimental design used was completely randomized design with four replications. Treatments consisted of clethodim + fenoxaprop-p-ethyl (50 + 50 g a.i. ha-1), sethoxydim (184 g a.i. ha-1), quizalofop-p-ethyl (75 g a.i. ha-1), nicosulfuron (50 g a.i. ha-1), fluazifop-p-butyl (125 g a.i. ha-1), fomesafen (225 g a.i. ha-1), haloxyfop-methyl (48 g a.i. ha-1), bentazon (720 g a.i. ha-1), chlorimuron-ethyl (15 g a.i. ha-1), and control without herbicide. The analyzed characteristics were stem diameter, plant height, and phytointoxication at 7, 14, 21, 28, 35, and 42 days after herbicide application (DAA), in addition to shootdry matter accumulation in seedlings at the end of the study. Nicosulfuron and chlorimuron-ethyl caused intoxication in all the studied tree species. In Jaboticabal, these herbicides impaired the initial growth of Jamaican nettletree seedlings, while no herbicide delayed its initial development in Junqueirópolis.A similar result was obtained regarding dry matter accumulation for garapeira in both cities. The herbicides clethodim + fenoxaprop-p-ethyl and sethoxydim decreased dry matter accumulation in Peruvian peppertree plants in Jaboticabal and Junqueirópolis, respectively, thus not being recommendedtheir use for these species.
Seletividade de herbicidas a espécies arbóreas nativas do Brasil
Keywords: Apuleia leiocarpa; Phytointoxication; Schinus mole; Tree species; Trema micrantha